Advances in siRNA Drug Delivery Strategies for Targeted TNBC Therapy - Md Abdus Subhan; Vladimir P. Torchilin (Bioengineering, 2024)
Among breast cancers, triple-negative breast cancer (TNBC) has been recognized as the most aggressive type with a poor prognosis and low survival rate. Targeted therapy for TNBC is challenging because it lacks estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Chemotherapy, radiation therapy, and surgery are the common therapies for TNBC. Although TNBC is prone to chemotherapy, drug resistance and recurrence are commonly associated with treatment failure. Combination therapy approaches using chemotherapy, mAbs, ADC, and antibody–siRNA conjugates may be effective in TNBC. Recent advances with siRNA-based therapy approaches are promising for TNBC therapy with better prognosis and reduced mortality. This review discusses advances in nanomaterial- and nanobiomaterial-based siRNA delivery platforms for TNBC therapy exploring targeted therapy approaches for major genes, proteins, and TFs upregulated in TNBC tumors, which engage in molecular pathways associated with low TNBC prognosis. Bioengineered siRNA drugs targeting one or several genes simultaneously can downregulate desired genes, significantly reducing disease progression.